Women as Religious Authorities in Islam. - Mirjam Künkler (Journal of Science and Knowledge Horizons, 2025)
Although the history of Islam includes numerous examples of women transmitting hadith, writing authoritative scholarly commentaries on the Qur’an and religious law, and issuing fatwas, the historical role of women as religious authorities is in general little acknowledged and women rarely perform such actions today. Most Muslim countries, including those in the Middle East, do not allow women to serve as judges in Islamic courts. Likewise, only few congregations would turn to women for advice on matters of Islamic law, or invite women to lead prayer, or deliver the sermon (khutba).  For decades, Sudan and Indonesia were the only countries that permitted female judges to render decisions on the basis of the Qur’an and hadiths (which is usually conceived as a male prerogative only). And only recently have religious seminaries in Turkey, Morocco, Iran, and pre-war Syria opened their highest degree programs to women, thus enabling women to develop the expertise in Islamic law required to  issue fatwas.